2020
DOI: 10.2174/1574888x15666191227113742
|View full text |Cite
|
Sign up to set email alerts
|

The Role of lncRNAs in Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells

Abstract: Bone Marrow Mesenchymal Stem Cells (BMSCs) are one of the primary cells found in the bone marrow, and they can differentiate into osteoblasts, chondrocytes, adipocytes and even myoblasts, and are, therefore, considered pluripotent cells. Because of their multipotential differentiation, selfrenewal capability, immunomodulation and other potential activities, BMSCs have become an important source of seed cells for gene therapy, tissue engineering, cell replacement therapy and regenerative medicine. Long non-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Growing amounts of evidences have shown that lncRNAs are important regulators in diverse biological processes and diseases including osteoporosis 5 7 . A good number of lncRNAs have been demonstrated to play critical roles in the osteogenic differentiation of BMSCs 8 10 . For example, lncRNA MALAT1 was downregulated in BMSCs from osteoporosis rats compared with the normal rats, and could inhibit osteogenesis through MAPK signaling 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Growing amounts of evidences have shown that lncRNAs are important regulators in diverse biological processes and diseases including osteoporosis 5 7 . A good number of lncRNAs have been demonstrated to play critical roles in the osteogenic differentiation of BMSCs 8 10 . For example, lncRNA MALAT1 was downregulated in BMSCs from osteoporosis rats compared with the normal rats, and could inhibit osteogenesis through MAPK signaling 11 .…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence that microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) are closely related to the occurrence and development of various diseases, including in ammatory diseases, metabolic diseases, and cancer [57][58][59]. Long non-coding RNA (lncRNA) is an RNA molecule greater than 200 nucleotides in length and recent studies have also shown that lncRNAs play an important role in the osteogenic differentiation of BMMSCs [60][61][62]. Growing research has demonstrated that lncRNA modulates gene expression at multiple levels such as epigenetic, transcriptional and post transcriptional [63].…”
Section: Discussionmentioning
confidence: 99%
“…As an important subset of non-coding RNAs (ncRNAs), long ncRNAs (lncRNAs) exceeding 200 nucleotides in length play important roles in various biological and pathological processes including osteogenesis [ 3 ] and the osteogenic differentiation of hBMSCs [ 4 6 ]. A recent study showed that lncRNA MIR22HG promotes osteogenic differentiation by downregulating phosphatase and tensin homolog, thereby activating AKT signaling [ 6 ].…”
Section: Introductionmentioning
confidence: 99%